Regional productivity growth in the EU: An assessment of recent developments - Ilias Kostarakos (European Commission, Joint Research Centre (JRC), 2023)
The level and growth rates of Total Factor Productivity estimates have been extensively used as a means of assessing the level of efficiency in production across regions as well as a source of the observed differences in economic performance. This paper, focusing on a sample of 242 EU NUTS2 regions spanning the 2000-2020 period provides a time series of TFP estimates, based on a new dataset of regional level capital stocks, and documents significant heterogeneity in terms of TFP developments across regions and groups of regions. The evidence suggest that TFP can account for up to 80% of the observed income differences, while it is made evident that during the period covered by the sample convergence in terms of TFP was weakened.
Keywords: E01; E10; O47; 330; production function; total factor productivity; development accounting; convergence